Wokół badań nad „Commentariolum Petitionis” - Appel, Hanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
Doubts concerning the authorship of the work contemporarily entitled Commentariolum Petitionis were raised even in the late nineteenth century. Both those researchers who regarded Quintus (Cicero’s brother) as the author and those who questioned his authorship found their supporters. In this context, Michael Alexander stands out, arguing in his publications that the intention behind the pamphlet was to provide a distanced or even warped image of late-Republican electioneering. The debate continues, and the importance of the present-day interpretation must be emphasised. Even if perhaps satisfactory for those who attribute the authorship to Marcus Cicero, recent computerassisted stylometric studies in fact fail to provide a conclusive answer as to who the author of the Commentariolum Petitionis actually was. Stylometric evidence may even be quoted to prove that it might have been written by someone skilful enough to imitate the eminent orator’s style.